(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The current review questions the implementation, benefits, and difficulties of the Goods and Services Tax (GST) in India through the synthesis of the available empirical evidence provided by the research papers published between 2014 and 2023. Key findings depict GST as a radical reform, which aims at creating a single, open tax system that operates on the principle of One Nation, One Tax hence eradicating cascading effects and promoting economic growth through indirect taxation simplification. The benefits described are: augmented tax receipts, reduced corruption, increased supply-chain performance, and long-term benefits to the sectors that can be large enterprises and micro-, small-, and medium-sized enterprises (MSMEs), which are better input-tax credits and formalisation of informal activity. However, identified impediments include the initial compliance limitations, high prices of MSMEs, insufficient infrastructures, and short-lived inflationary pressures especially in areas in which the unorganised sector forms the major part. Researchers highlight the urgency of the administrative interventions, education of the stakeholders and continuous improvements to achieve the maximum potential of GST. On the whole, despite the initial obstacles to its implementation, GST can be described as a positive step towards economic growth, and it is through its effective implementation that scholars believe that the Indian economy will be able to develop sustainably and become more competitive in the global marketplace.